Simulation of nuclear reactor control and protection system - Bubelis, Evaldas; Listopadskis, Narimantas; Pabarčius, Raimondas (Lietuvos matematikos rinkinys, 2004)
Ignalina NPP RBMK-1500 reactor control and protection system (RCPS) logic, which was implemented in code QUABOX/CUBBOX-HYCA, is described in the paper. Analysis of numerical simulation results shows, that logic of RBMK-1500 RPSS is adequate to logic as described in technical literature. Simulation results obtained by code QUABOX/CUBBOX-HYCA were compared with simulation results obtained using STEPAN code. The conclusion was made that RCPS operation sequences and response are analogical. The complement the code QUABOX/CUBBOX-HYCA with full realistic RCPS logic allows to simulate the transient processes and accidents, which have place in the reactor core of Ignalina nuclear power plant.